Mastering Life Skills as Social Rehabilitation of Persons with Disabilities at a Social Institution - Nada Nabilah Az-Zahra (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2021)
The purpose of this study was to find out the function of social rehabilitation services for persons with disabilities at the Social Institution for the rehabilitation of persons with disabilities in Cibabat Cimahi, to find out the implementation of the social rehabilitation program for persons with disabilities, and to find out changes in the behavior of persons with disabilities after receiving the service program at the Social Institutions for persons with disabilities Cibabat Cimahi. This research was conducted using a descriptive method with a qualitative approach. This research resulted from the exposure of informants conducted by interviews, not in the form of numbers. Collecting data in this study utilizing observation, interviews, literature study, and documentation. Data analysis in this study included collecting all data and reducing data to conclusions as a result of the research. Based on this research, clients with disabilities, before entering and not carrying out the service program at the Social Institution for the rehabilitation of persons with disabilities Cibabat Cimahi, most clients have not been able to carry out activities independently in carrying out their daily activities and do not yet have the ability or expertise. After entering and implementing the program, clients with disabilities participate in service programs, namely physical guidance, mental guidance, social guidance, and skills programs which include sewing, mechanics, handicrafts, housekeeping, electrical, carpentry and cosmetology. After participating in the service program, clients with disabilities will be proven whether clients with disabilities can change their behavior for the better.